Soil water content and longitudinal microbiota distribution in disturbed areas of tower foundations of power transmission and transformation projects - Che Kai; Yu Jinxing; Ju Yukun; Zhao Xuan; Gong Yunqian; Chen Chongming (Open Geosciences)
In power transmission and transformation engineering, tower foundation construction activities are frequent, and their interference with the surrounding soil environment is becoming increasingly prominent. During the construction of such projects, tower foundation construction involves site excavation, foundation pouring, and backfilling operations, which can damage the original structure of the soil, change the moisture and nutrient status, and thus affect the soil ecosystem. To gain a profound understanding of the impact of engineering activities on soil environments and ensure soil ecosystem stability, this article investigated the distribution characteristics of soil moisture content and vertical microbial communities in the disturbed areas of transmission and transformation tower foundations. Soil samples were collected from the study region, and the extent of soil collapse, crack density, and soil moisture content were calculated using the dry method after post-disturbance vegetation restoration. The study determined the microbial distribution characteristics in areas with soil collapse and vegetation degradation, and analyzed the impact of varying distances from the disturbance center on microbial distribution. Experiments revealed that under the influence of tower foundation construction, areas with extreme soil subsidence and high crack density exhibited lower soil moisture content. During the construction process of the tower foundation for power transmission and transformation projects, mechanical operations such as rolling and excavation directly damage the root system of vegetation, making it difficult for plants to grow stably and hindering their absorption of water and nutrients from the soil, thereby affecting their normal physiological activities and leading to poor or even degraded vegetation growth. In areas with severe soil subsidence, the microbial populations of bacteria, actinomycetes, and disturbance of the tower foundation construction disrupt the pore system of the soil, making the soil close to the disturbed area less aerobic and permeable, and the microbial living space is compressed. The survival space of microorganisms is compressed and thus reduced. As the distance increases, the degree of soil disturbance gradually decreases, resulting in an increase in the number of microorganisms. Interference activities such as tower foundation construction in power transmission and transformation projects have damaged vegetation, resulting in vegetation degradation, significant reduction in leaf litter, and severe shortage of organic matter supply in the soil. The growth and reproduction of microbial communities are highly dependent on the energy and nutrient deficiencies provided by organic matter, leading to a decrease in their distribution.